The ITER Tokamak Exhaust Processing System Design and Substantiation. (17th November 2019) - Wilson, Jason; Becnel, James; Demange, David; Rogers, Bernice
Abstract: The ITER fuel cycle is composed of a tokamak and several systems that will support the preparation of fuel, the handling of exhaust gases, and the recycle of unused fuel back to the tokamak. Deuterium and tritium (DT) isotopes are supplied to the tokamak. A key need for such separations arises from the fact that, of the DT fed to the ITER tokamak, only a small fraction burns. The unburned DT exits the tokamak along with impurity gases. The impurities are a rather complicated mixture including helium ash, non-DT gases injected into the tokamak, species originating from chemical reactions, and species originating from nuclear reactions. Exhaust gases from the torus are collected by pumps, which move the exhaust material to the tokamak exhaust process (TEP) system. The TEP system performs chemical separations on ITER fuel cycle process streams. The TEP recovers hydrogen isotopes from impurities such as argon, nitrogen, water, ammonia, and hydrocarbons. The TEP sends the hydrogen isotopes for subsequent processing to the isotope separation system or the storage and delivery system. At the same time, an impurity gas stream of extremely low tritium content (less than 8.88 TBq of tritium per day) is sent to the detritiation system. Since the TEP system completed conceptual design in 2010, the overall ITER design has advanced on a number of fronts. These advancements have affected the interfacing systems and operational scenarios that could have affected the design of the TEP system. The interfacing and operational changes were examined and new performance requirements for the TEP were determined. The TEP design was evaluated to determine if the design was flexible and robust enough to meet the performance and discharge requirements.